Organizacje globalnego zarządzania ekonomicznego w ładzie policentrycznym na przykładzie polityki wobec inwestycji zagranicznych. Wyzwania i inicjatywy w obszarze koordynacji polityki wobec bezpośrednich inwestycji zagranicznych - Götz, Marta (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2017)
This paper touches upon the international coordination of policies pursued to - wards foreign direct investment (FDI). The solutions presented allow us to state that the efforts taken in the international arena in coordinating FDI policies constitute an example of economic order in a polycentric world. The inclusion of direct invest - ment in the EU’s common commercial policy, or of investor-state dispute settlements in the TTIP negotiations, indicate that management of FDI can be a planned, long- term process. Yet, at the same time, such phenomena as the economic and financial crisis of 2008, or the unprecedented dynamics and scale of the expansion of Chinese businesses show that global economic governance in this field must swiftly adapt to changing circumstances. Designing, developing and coordinating activities in the field of investment policy, which is a manifestation of global economic management, is conditioned by long-term strategies and trends, as well as adapting to emerging challenges
Organizations of global economic polycentric governance on the example of foreign investments policy. Challenges and initiatives in the area of the coordination of foreign direct investment (FDI) policy
Keywords: FDI (foreign direct investment); policy; governance; coordination